EVALUASI SISTEM PENGENDALIAN INTERNAL ATAS PENJUALAN KREDIT STUDI KASUS PADA PT. “Y” SEMARANG - Endang Kurniawati (STIE Pelita Nusantara Semarang, 2010)
Target of company for example to obtain; get profit is generally obtained from sale activity, good of cash sale and also credit. this is Sale activity very easy to the happening of deviation, extravagance, and is not effective. of which can harm company as a whole. For meminimalisasi the happening of all kind of the deviation needed by an adequate internal operation system. the Internal operation consist of an designed procedure and policy so that/ to be can give guarantee to push company operational efficiency, providing reliable data as decision making base, and push implementation of policys which have been specified previously